Unbuttoned : the art and artists of theatrical costume design - Pollatsek, E. Shura; Wilson, Mitchell D. (New York : Routledge, Taylor & Francis Group, 2017)
This book documents the creative journey of costume creation from concept to performance. Each chapter provides an overview of the process, including designing and shopping; draping, cutting, dyeing, and painting; and beading, sewing, and creating embellishments and accessories. This book features interviews with practitioners from Broadway and regional theatres to opera and ballet companies, offering valuable insights into the costume design profession. Exceptional behind-the-scenes photography illustrates top costume designers and craftspeople at work, along with gorgeous costumes in progress.
1. Design -- Creating the vision -- The bold colorist : Richard Hudson -- A passion for collaboration : Julie Scobeltzine -- Revealing characters : Fabio Toblini -- Continually exploring : David C. Woolard -- Bringing it all together : Alain Germain -- 2. Sourcing materials -- Filling in the outlines -- Supporting the design : shopper Sarah Bahr -- A library of textiles : Eduardo Madrid at B & J Fabrics -- Supplying the choices : purchasing manager Tim Blacker -- 3. Draping and cutting -- Sculpting the shape -- Costume architect : Kjersten Lester-Moratzka -- Transforming bodies : Triffin Morris -- Translating the sketch : David Arevalo -- 4. Fabric embellishment -- Crating a custom surface -- Lizards and cats : painter Parmelee Tolkan -- From traditional to digital : painter-dyer Caroline Dignes -- Sparkle and texture : bead manager Polly Isham Kinney -- 5. Construction -- Building the garment -- Couture and stage : costumer Quentin Desfray -- A love of sewing : stitcher Louisa Williams -- Part of the process : first hand Ashley Rigg -- 6. Crafts and millinery -- Creating accessories -- Testing the molds : milliner Arnold Levine -- Drilling and melting : the Crafts Department at Parsons-Meares, Ltd. -- Hats, headdresses, and helmets : milliner Deborah Nash -- Leather as a medium : craftsman Yann Boulet -- Building masks, building relationships : craftsman Brian Russman -- 7. Wigs and hair -- Finishing the look -- Rotating repertory : David Zimmerman -- The danger of live performance : Christine "Micki" Chomicki -- Finding the context : Heather Fleming -- 8. Putting it all together -- Creating a character.
"A Focal Press Book"--Cover.
Includes bibliographical references and index.
Keywords: Costume; Costume design; PERFORMING ARTS -- Theater -- Direction & Production; PERFORMING ARTS -- Theater -- Stagecraft & Scenography; Costume; Costume design; Costume design; Costume